Perbandingan Reaksi Transfusi Darah pada Pasien Thalasemia dengan Pemberian Darah PRC Biasa dan Darah PRC Leukodepleted - Laksana, Roni Windi; Baehaki, Farhan (Jurnal Kesehatan Rajawali, 2024)
Packed Red Cell (PRC) blood transfusion is the main therapy for thalassemia patients to increase hemoglobin levels and prolong life. PRC blood contains high levels of leukocytes so it has the potential to cause allergic reactions and fever post-transfusion. Therefore, the alternative is usually to use PRC Leukodepleted (PRC-LD) blood because it has a very low leukocyte content, making it possible to reduce the risk of transfusion reactions. This study was conducted to compare the incidence of transfusion reactions between administration of regular PRC blood and PRC-LD blood in thalassemia patients. This research is a retrospective study with a quantitative approach and descriptive design. Data collection was carried out by looking at medical records for the period January-December 2023. The data collected was analyzed descriptively to look at the characteristics of the data in depth. In addition, statistical analysis was carried out using the Chi-Square Test to analyze the effect of using regular PRC and PRC-LD. It was found that there was a significant difference (sig. <0.01) in the incidence of transfusion reactions using regular PRC blood and PRC-LD. Descriptive data shows that the risk of transfusion reactions when using PRC-LD blood is lower than regular PRC. Thus, it can be concluded that the use of PRC-LD blood has been proven to reduce the incidence of transfusion reactions in thalassemia patients compared to regular PRC blood.